Bandwidth Management with Mikrotik OS Routers Using the Per Connection Queue Method - Sapriyadi, Sapriyadi; Zuhro, Siti Fatimatul; Naim, Abu; Nurfy, Ariadin; Supriyade, Supriyade; Husodo, Purwani; Wardhani, Annisa Risqi Sulistya Kusuma; Budianto, Rizki (Formosa Journal of Science and Technology, 2024)
Services that use the Internet as Business Cafe, Online Games, education, defense and security, online businesses, e-mail service providers, and others will experience barriers in carrying out their activities. Often problems arise in internet service providers are setting up or managing broadband. The implementation of broadband management is aimed at optimizing the bandwidth available to provide broadband guarantees for Internet users, such as network congestion (through traffic) and unstable broadband received by Internet service providers (ISPs). Bandwidth management in Mikrotik with the PCQ (Per Connection Queue) method, basically, uses queue methods for the bandwidth balance used on multiple clients. The main purpose of this method is to automatically and unevenly share bandwidth sharing, with a simple turn-line if only one subscriber actively uses another temporary bandwidth will be in the standby position, then the subscriber can use maximum bandwidth which is available, but if another customer is active, then the maximum bandwidth can be used by both customers who have maximum width / 2, if there are subscribers at the same time active, each will receive the maximum bandwidth allowance / all clients, so will not be a fair wide-ranging distribution for all customers.